A comparative evaluation of intraoral and extraoral digital impressions: An in vivo study - Gursharan Kaur Sason; Gaurang Mistry; Rubina Tabassum; Omkar Shetty (Wolters Kluwer Medknow Publications, 2018)
Aim: The accuracy of a dental impression is determined by two factors: "trueness" and "precision." The scanners used in dentistry are relatively new in market, and very few studies have compared the "precision" and "trueness" of intraoral scanner with the extraoral scanner. The aim of this study was to evaluate and compare accuracy of intraoral and extraoral digital impressions. Materials and Methods: Ten dentulous participants (male/female) aged 18-45 years with an asymptomatic endodontically treated mandibular first molars with adjacent teeth present were selected for this study. The prepared test tooth was measured using a digital Vernier caliper to obtain reference datasets. The tooth was then scanned using the intraoral scanner, and the extraoral scans were obtained using the casts made from the impressions. The datasets were divided into four groups and then statistically analyzed. The test tooth preparation was done, and dimples were made using a round diamond point on the bucco-occlusal, mesio-occlusal, disto-occlusal, and linguo-occlusal lines angles, and these were used to obtain reference datasets intraorally using a digital Vernier caliper. The test tooth was then scanned with the IO scanner (CS 3500, Carestream dental) thrice and also impressions were made using addition silicone impression material (3M™ ESPE) and dental casts were poured in Type IV dental stone (Kalrock-Kalabhai Karson India Pvt. Ltd., India) which were later scanned with the EO scanner (LAVA™ Scan ST Design system [3M™ ESPE]) thrice. The Datasets obtained from Intraoral and Extraoral scanner were exported to Dental Wings software and readings were obtained. Repeated measures ANOVA test was used to compare differences between the groups and independent t-test for comparison between the readings of intraoral and extraoral scanner. Least significant difference test was used for comparison between reference datasets with intraoral and extraoral scanner, respectively. A level of statistical significance of P < 0.05 was set. Results: The precision values ranged from 20.7 to 33.35 μm for intraoral scanner and 19.5 to 37 μm for extraoral scanner. The mean deviations for intraoral scanner were 19.6 μm mesiodistally (MD) and 16.4 μm buccolingually (BL) and 24.0 μm MD and 22.5 μm BL for extraoral scanner. The mean values of the intraoral scanner (413 μm) for trueness were closest to the actual measurements (459 μm) than the extraoral scanner (396 μm). Conclusion: The intraoral scanner showed higher "precision" and "trueness" values when compared with the extraoral scanner.